2019
DOI: 10.1136/bjsports-2018-099943
|View full text |Cite
|
Sign up to set email alerts
|

High intensity exercise for 3 months reduces disease activity in axial spondyloarthritis (axSpA): a multicentre randomised trial of 100 patients

Abstract: BackgroundExercise is considered important in the management of patients with rheumatic diseases, but the effect of high intensity exercises on disease activity is unknown.ObjectiveTo investigate the effectiveness of high intensity exercises on disease activity in patients with axial spondyloarthritis (axSpA).MethodAssessor blinded multicentre randomised controlled trial. 100 patients (aged from their 20s to their 60s) with axSpA were randomly assigned to an exercise group or to a no-intervention control group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
129
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 113 publications
(137 citation statements)
references
References 38 publications
2
129
1
5
Order By: Relevance
“…Aerobic PA concerns PA executed with moderate or vigorous intensity. Recent studies suggest that vigorous-intensity PA is most effective in improving cardiorespiratory fitness and reducing cardiovascular risk [ 10 , 16 18 ] and it shows to be both beneficial and safe for people with axSpA [ 19 , 20 ]. Therefore, especially vigorous-intensity PA should be pursued by people with axSpA, at least by those without an increased risk of cardiovascular complications during exercise.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aerobic PA concerns PA executed with moderate or vigorous intensity. Recent studies suggest that vigorous-intensity PA is most effective in improving cardiorespiratory fitness and reducing cardiovascular risk [ 10 , 16 18 ] and it shows to be both beneficial and safe for people with axSpA [ 19 , 20 ]. Therefore, especially vigorous-intensity PA should be pursued by people with axSpA, at least by those without an increased risk of cardiovascular complications during exercise.…”
Section: Introductionmentioning
confidence: 99%
“…This is striking as relatively many axSpA patients have PT treatment [ 32 ] and it is generally acknowledged that apart from other health professionals, physical therapists play an important role in the promotion of PA [ 15 ]. However, it appears that aerobic PA may not be included in PT treatments often [ 32 ] and that the aerobic PA employed in exercise programs for people with axSpA is often inadequately dosed [ 20 , 33 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the strong link between inactivity and cardiovascular disease, which is prevalent comorbidity following these diseases [26,27], it is also growing evidence for the antiinflammatory effect of high-intensive exercise. The theoretical rationales for these mechanisms are thoroughly presented [28,29], and meta-analyses and clinical effect studies have demonstrated that intensive exercise is well tolerated and may reduce disease activity in axSpA patients [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…The medical treatment options have revolutionized the field of rheumatology in the last decades, and many patients experience reduced disease burden as a result of effective biological medication [30,31,36]. Still, the axSpA patients in the EMAS cohort report the negative impact of overweight and obesity on disease activity.…”
Section: Discussionmentioning
confidence: 99%
“…Participants exercise weekly in groups led by physiotherapists (PTs) in landbased or water-based settings. The objectives of the GET are to minimize the progressive spinal mobility restriction [17], reduce cardiovascular and biological risk factors [18], and maintain or increase muscle strength. According to the recommendations [3], annual fitness assessments are also part of the SVMB's quality concept.…”
Section: Introductionmentioning
confidence: 99%